Peran Orang Tua Dalam Membatasi Penggunaan Gadget Pada Raudhatul Athfal Islamiyah Al-Amin - Nunzairina, Nunzairina; Nayla Zaskia Siregar, Fatimah; Afifah, Zahra (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2022)
Research that has observed children, there are children who are addicted to gadgets resulting in children being private and happy to be alone. The role of parents who build his enthusiasm to see the outside world again. Whatever the case, children can be happy, and for traditional play equipment it might be more fun. From here interviewing parents can be done to get to know the child better. Long-term or short-term complex, children will get bored with their gadgets more and more. With the existence of gadgets, everyone is always very quick to retrieve information, but there is a lot that can affect all children. One step for today's children who are not directly related to flat objects/handphone. Parents have given gadgets to their children, with the excuse that they are not fussy. And the observations that have been purely carried out by researchers make awareness, the need for children not to understand gadgets from childhood. There are many cases of children who are already familiar with gadgets, and have a negative impact on them. Thurs children must be monitored continuously using gadgets